Parents of foreign "terrorist" fighters in Syria – will they report their young?. Issue 1 (2nd January 2017) - Awan, Imran; Guru, Surinder
ABSTRACT: The mounting tide of foreign fighters leaving Britain for the Middle East to fight, sacrifice or find new lives has blighted European governments and led to the further tightening up of counter-terrorism measures. Since the first British arrest of a Syrian returnee (Choudhury) in 2014, the latest figures of foreign fighter returnees have surged to approximately 800. A number of strategies aimed at thwarting these trends have surfaced including a call upon Muslim parents to scrutinise their children's attitudes and behaviour and to be watchful of their radicalization. Based on a study in the West Midlands (in the UK), the paper provides a snapshot of how Muslim parents have received calls upon them to report their actual or potentially radicalized children to the police. We argue that current practices are likely to be ineffective unless more democratic spaces are provided for free political expression.